Blade of the immortal omnibus. IX - Samura, Hiroaki; Saito, Tomoko; Simon, Philip R (Dark Horse Manga, 2019)
"Manji and Rin may have a fighting chance, but can a wounded and road-weary Magatsu hold his own against an invigorated, freshly armed foe?"--Back cover.